Draft Seventh Five Year Plan (1985-90) and Annual Plan (1985-86) Volume - VIII Hill Areas Power, Industry and Minerals Government of Assam - Planning Commission (Planning Commission, 1985)
The latest cost estimate for the project is Rs.275 lakhs including the 4th unit. During the current year a provision of Rs. 22 lakhs has been made against this scheme. As the project will be fully commissioned during, 1984-85 there will be no still over to seventh Five year plan. As such no proposal has been made for allocation during the Seventh Five year plan and 1985-86 plan.
Government of Assam